Prevention Of Miscommunication Through Feedback Control In Virtual Learning - Abdul Fattah; Ardiyan Ainul Yaqin; Faricha Fahmadina (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2025)
Miscommunication is an inherent and significant challenge in virtual learning environments, often exacerbated by the lack of non-verbal cues and interaction delays. Such miscommunication can drastically hinder material comprehension, lower the quality of interaction, and reduce the overall effectiveness of the educational process, ultimately leading to a decline in learning outcomes. Therefore, this research is crucial as it addresses a core issue in E-Learning. By examining the role of feedback control, this study offers structured and practical solutions to minimize instructional ambiguity and the understanding gap between educators and learners in virtual settings.The primary objective of this research is to analyze and demonstrate the effectiveness of preventing miscommunication through intentional and structured feedback control—encompassing teacher-to-student, student-to-teacher, and peer- to-peer feedback. The findings highlight miscommunication prevention strategies and mechanisms that are generally applicable in virtual learning. Effective feedback control includes providing prompt, clear, and bidirectional responses, alongside the use of interactive media that facilitates message clarification. By implementing feedback control, incidents of miscommunication, such as instructional misunderstandings and material ambiguity, can be minimized.It is predicted that the results will show that directed and consistent feedback plays a vital role in preventing miscommunication. With the application of clear, reciprocal feedback strategies, students will more easily comprehend messages conveyed by educators and feel more motivated to provide meaningful feedback in return. Generally, this research is expected to underscore the importance of feedback management for effective two-way communication in virtual learning, thereby contributing to the development of more effective and efficient digital educational communication strategies.